A Comparative Analysis of the Effectiveness of Virgin Coconut Oil (VCO) and Olive Oil on the Degree of Striae Gravidarum - Rasyidah, Rasyidah; Laylatul Hasanah; Sri Sumarni; Abd. Wahid (Indonesian Academia Health Sciences Journal, 2024)
Background: Striae gravidarum is the stretching of the skin beyond its elastic limit that causes blue or reddish lines to appear on the abdomen, thighs, and breasts of pregnant women. Striae gravidarum can cause itching, burning, and dryness, as well as emotional disturbances that cause discomfort in most pregnant women. The prevalence of Striae gravidarum in pregnant women worldwide ranges from 50% to 90% but specific data on Striae gravidarum is not recorded because Striae gravidarum is a complaint or discomfort during pregnancy that is sometimes ignored by pregnant women themselves. Virgin Coconut Oil (VCO) is coconut oil that contains ingredients that effectively maintain skin elasticity. This study is a development of research that has been conducted previously by researchers related to Striae gravidarum and Virgin Coconut Oil. Aims: The purpose of this study was to conduct a comparative study regarding the more significant effectiveness of using Virgin Coconut Oil and Olive Oil on the degree of Striae gravidarum. Methods: This research uses quasi experiment. with Pretest Posttest Control Group Design. The population of this study were all pregnant women in Errabu Village, Bluto District, Sumenep Regency. The sample is Trimester II pregnant women in Errabu Village using purposive sampling method. Data analysis will use a significance level of <0.5 then compare whether VCO or Olive Oil has the most significant effect in reducing the degree of Striae Gravidarum. Results: The results of the analysis show that the p-value of 0.04 < α (0.05) so that H1 is accepted, H0 is rejected, which means there is a difference in the effectiveness of using Virgin Coconut Oil (VCO) and Olive Oil on reducing the degree of Striae Gravidarum in pregnant women, although both oils are equally effective in reducing the degree of striae gravidarum. Conclusion: VCO is more effective than olive oil in reducing the degree of striae gravidarum in second trimester pregnant women in Errabu Village, Sumenep District. Keyword: Virgin Coconut Oil; Olive Oil; Striae Gravidarum